Exports and property prices in France: Are they connected? - Balázs Égert; Rafal Kierzenkowski (Center for Economic Studies and ifo Institute (CESifo), 2010)
France has seen a marked deterioration in its export performance in the last 10 years or so. Previous empirical research pointed out that weak export performance was due to i) vigorous domestic demand; ii) lower mark-ups due to head-to-head competition with Germany; iii) low non-price competitiveness of French export goods; iv) offshoring of entire production processes (especially in the automobile sector); and v) difficulties of French manufacturing firms to reach critical size for exporting. This paper adds an additional explanation to this list. We argue that resource reallocation from the exporting to the construction sector triggered by fast rising property prices hindered France to meet world export demand vis-à-vis its products. Our econometric analysis shows that the resource reallocation argument helps explain French export performance between the early 2000s and 2007, unexplained by traditional models. This result is confirmed for a set of OECD countries that experienced a marked decline in their export performance and sustained real-estate boom after 2000.
Keywords: F10; F14; O14; O52; 330; OECD; France; competitiveness; exports; export performance; construction; house prices; resource allocation; Außenhandelswirtschaft; Exportindustrie; Internationaler Wettbewerb; Immobilienpreis; Bubbles; Allokation; Bauwirtschaft; Frankreich; Vergleich; OECD-Staaten